Socialization and Assistance in the Processing of Organic Waste Into Eco-Enzyme in 16 Ulu Village, Seberang Ulu II Sub-District, Palembang City - Palmasari, Berliana; Amir, Nurbaiti; Gusmiatun, Gusmiatun; Paridawati, Ika; Fahmi, Innike Abdillah; Syafrullah, Syafrullah; Sofian, Ahmad (Altifani Journal: International Journal of Community Engagement, 2022)
Organic waste is waste that contains elements of carbon, hydrogen and oxygen and is easily degraded by microorganisms. The existence of abundant fruit and vegetable waste is rarely used by the community, even though this organic waste can still be reused as material for making eco-enzymes. Eco-enzyme is a liquid extract produced from the fermentation of leftover vegetables and fruits with brown sugar or molasses as a substrate. The process for making eco-enzymes is in principle similar to how compost is made, but water is added as a growth medium so that the final product is a liquid that is easy to use and has many benefits. This activity aims to provide knowledge and skills to the community about reusing household organic waste by processing it into eco-enzymes. The location of the community service was carried out in one of the houses of the residents of RT.071 RW.016, 16 Ulu Village, Seberang Ulu II District, Palembang City, on September 4 2021. The method used was counseling and training for the community about processing organic waste into eco-enzymes. This activity was attended by 15 participants who actively conducted discussions. The results of this community service show that the method of service in the form of counseling, training and question and answer is very appropriate in providing motivation to the community in processing household organic waste into eco-enzymes.